Training And Mentoring Of Making Doormats From Patchwork For Creative Business For Housewife In Pangmilang Singkawang - Rosmaiyadi Rosmaiyadi; Dian Mayasari; Susan Neni Triani; Emi Sulistri; Insan Suwanto (STKIP Singkawang, 2018)
Training and mentoring program aims to facilitate the community in Pangmilang Village Singkawang especially for mothers of households to take advantage of the patchwork that often is not considered useful to be harnessed into a doormat. The patchwork can be collected from the local tailor was in the village Pangmilang, so it has the potential to be used as an extra income by making doormats. The resulting mat has three different types and models of doormats, i.e. the model's braids, mats models and model leaves. In the implementation of training and mentoring still-based household industries with capital and limited production, the production process is still very simple. The program is realized through the method of STM (socialization, training, and mentoring), namely through the practice directly in the field. Results obtained from the training and mentoring programs are the housewives are already skilled in making doormats made from patchwork foot and it can market products produced in the region around the Village Pangmilang.